The effect of third intensity zone exercises by varying the muscle elongation of the muscles of the dominant arm and the supporting leg on some physiological indicators and the performance of pushing the weight - al-Azzawi , Nimet (Journal of Physical Education, 2024)
The research aimed to prepare exercises for the third intensity area with the variation of muscle elongation of the prevailing arm muscles and the supporting leg of the weight push players, and to identify the effect of the exercises of the third intensity area by contrasting the muscle elongation of the dominant arm muscles and the supporting leg in some physiological indicators and the achievement of weight pushing, and the researcher assumed that there are statistically significant differences between the results of the pre- and post-tests for the top and the time of the signal (EMG) for each of the dominant arm muscles and the supporting leg (brachial, radial brachial of the dominant arm, and rectilinear femurs). anterior, and twin leg) at the moment of the start of the rotation phase to push the weight of the players of the experimental group, and there are statistically significant differences between the results of the pre- and post-tests to accomplish the weight push distance for the players of the experimental group, the experimental research approach was adopted by designing one experimental group with tight control of the pre- and post-tests, The limits of the research community were represented by the young players in the hammer throwing event in the Etisalat Club, who numbered (9) players for the sports season (2023/2024), all of whom were deliberately selected for the research sample by (100%) from their original community in a comprehensive inventory method to represent the experimental research group, and to measure the electrical indicators of both the dominant arm muscles and the supporting leg (brachial, radial brachial of the dominant arm, anterior femoral rectum, and leg twin) The moment the rotation phase begins to push the weight The researcher adopted the (EMG) device and to measure the achievement the test was adopted Completion of the hammer throwing event in accordance with the conditions of competition in the international law of the Athletics Federation according to its international bulletin for the year (2018), and the exercises were prepared and applied with a field experiment that began with the application of the pre-tests on (16/11/2023), and then the application of these exercises for the period from (19/11/2023) to (11/1/2024), and the completion of the experiment by applying the post-tests on (14/1/2024), then the results were processed with the (SPSS) system. Extracts and applications are formed by the fact that the third severity area exercises help with the contrast of the muscular elongation of the prevailing arm muscles and the supporting man in increasing the summit of the EMG sign and reducing its time for both the prevailing arm muscles and the supporting man (the humerus, and the Hebrew muscles of the prevailing arm, the front thighs, and the twins of the leg) in the players The moment of the start of the rotation stage to push the weight, and helps in the development of the distance of the completion of the heavy -paying the players, and it is necessary to pay attention to the coaches of the heaviness in the physiological measurement by measuring the (EMG) signals for the prevailing arm muscles and the man who supported the players to pay the weight and plan and apply the exercises according to the physiological characteristics by adopting the results of this measurement, It is necessary not to exaggerate the training loads or how much muscular elongation resistors to reduce the problem of decreasing the speed of muscle rubble in the event of an increase in the amount of these resistors.